Meningkatkan Keterampilan Literasi Baca Tulis Pada Anak Melalui Pojok Baca di SD Negeri 060884 - Christin Debora Purba; Rahma Hayati Harahap (Jurnal Pengabdian Masyarakat dan Inovasi, 2023)
Literacy is one of the important aspects that must be applied in elementary schools. Which through reading literacy activities students will get used to reading and add to student information. This literacy activity also has the benefit of increasing interest and talent in students from an early age. Because most of the educational process depends on literacy skills and awareness. The literacy culture that is embedded in students can influence the level of success and students' ability to understand information analytically, critically, and reflectively. Nowadays, children tend to be more interested in playing mobile phones than reading, as is the case with students at SD Negeri 060884. Therefore, assistance is needed to increase their literacy interest in reading and writing. The process of providing this assistance was also carried out in the PKL I mini project activities, using the casework method which consisted of Engagement Intake Contracts, Assessment, Planning/Planning, Intervention, Evaluation, Termination. The focus of the client's problem solving process is to give them some decent children's story books for them to read which in the story books also contain pictures which of course can interest them to read them. The aim of this program was stated to have been achieved, due to the increased enthusiasm of the client to do literacy reading.